2015
DOI: 10.1111/jog.12810
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transcutaneous electrical acupoint stimulation on ovarian reserve of patients with diminished ovarian reserve in in vitro fertilization and embryo transfer cycles

Abstract: TEAS and AEC treatments could improve basal endocrine levels in patients, and increase the number of oocytes retrieved and high-quality embryos. TEAS treatment could improve the clinical pregnancy rate in patients with decreased ovarian reserve during in vitro fertilization and embryo transfer cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…In recent years, several articles have reported the positive role of TEAS in IVF [28][29][30], confirming our initial assumption and indicating that we should focus on comfort acupuncture for infertility, not like paralytic diseases, and the stronger the stimulation, the better the effect [31]. e patient should feel relaxed or unstressed and be adapted to the technique and acupuncturist before the IVF cycle begins.…”
Section: Future Directionssupporting
confidence: 76%
“…In recent years, several articles have reported the positive role of TEAS in IVF [28][29][30], confirming our initial assumption and indicating that we should focus on comfort acupuncture for infertility, not like paralytic diseases, and the stronger the stimulation, the better the effect [31]. e patient should feel relaxed or unstressed and be adapted to the technique and acupuncturist before the IVF cycle begins.…”
Section: Future Directionssupporting
confidence: 76%
“…27 TEAS treatment was found to improve CPR in the patients with decreased ovarian reserve during IVF. 28 In the present study, we found TEAS using a frequency of 2/100 Hz significantly improved the CPR, IR and LBR of the IVF women.…”
Section: Discussionsupporting
confidence: 59%
“…In recent years, with the rapid development of electrophysiology rehabilitation science and technology, treatment methods using electrophysiology as the main intervention method have attracted everyone's attention. Pelvic floor rehabilitation technology has been widely used in gynecological diseases and reproductive endocrine diseases, and has achieved good results [9] .…”
Section: Discussionmentioning
confidence: 99%